1995
DOI: 10.1161/01.atv.15.7.963
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lipoprotein B Binding to the LDL Receptor by Exogenous Lipids and Apolipoproteins CI, CII, CIII, and E

Abstract: We have recently shown that apo B-containing lipoproteins isolated by immunoaffinity chromatography bind to the LDL receptor with an affinity dependent on their apo E or apo CIII content. However, these lipoproteins--LpB:E, LpB:CIII, and LpB:CIII:E--isolated from whole plasma have variable lipid and apolipoprotein contents, and it is difficult to consider each parameter separately, particularly because an increase in the apo CIII content is always associated with an increase in the content of other C apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 27 publications
3
116
1
Order By: Relevance
“…Tissue culture media and reagents were purchased from Life Technologies, Inc., and fetal bovine serum was from Gemini Bioproducts (Calabasas, CA). Human native apoCIII (29), human recombinant nonpancreatic soluble PLA2 (sPLA 2 ) (30), and partially purified phospholipid transfer protein (31) were prepared as described previously. Soybean lipoxygenase and all other reagents were from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue culture media and reagents were purchased from Life Technologies, Inc., and fetal bovine serum was from Gemini Bioproducts (Calabasas, CA). Human native apoCIII (29), human recombinant nonpancreatic soluble PLA2 (sPLA 2 ) (30), and partially purified phospholipid transfer protein (31) were prepared as described previously. Soybean lipoxygenase and all other reagents were from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, [ 3 H]SM-emulsions (0.4 ml; 182 nmol of SM) were incubated with 200 g of apoCIII (22.5 nmol) for 2 h at 40°C. A portion of the emulsions was re-isolated from free apoCIII using ultrafiltration (29) as follows: the crude emulsion/apoCIII mixture was diluted to 2 ml with buffer containing 150 mM NaCl, 0.3 mM EDTA, pH 7.4, and ultrafiltered and concentrated to 0.2 ml using a Centricon 30 (molecular weight cut-off ϭ 30,000); the concentrated emulsions were then diluted to 2 ml, and the process was repeated 5 times. [ 3 H]SM-emulsions run through the same enrichment and re-isolation protocols in the absence of apoCIII served as the control for the experiments in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…19 Third, several studies have shown that apoC-III inhibits receptor-mediated uptake of TRL by the liver. 21,22 Kinetic studies using tracer methodology have confirmed that VLDL-apoC-III is overproduced in overweight insulin-resistant subjects, 15 in hypertriglyceridemic subjects compared with controls, 53 and in centrally, obese men compared with controls. 54 Increased plasma concentrations of apoC-III are associated with impaired VLDL1 clearance in obese insulin-resistant men 55 and VLDLapoC-III clearance is reduced in centrally obese men compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…Elevated apoC-III has been postulated to contribute to the atherogenic dyslipidemia by the impairment of TRL and HDL metabolism including increased VLDL production and secretion, 18 disturbance of TRL clearance by inhibiting LPL 19 or hepatic lipase, 20 and interfering with TRL and their remnant binding to hepatic lipoprotein receptors. 21,22 Beyond the effects of apoC-III on TRL and HDL metabolism, this apolipoprotein has also been shown to promote inflammation and endothelial cell dysfunction, potentially contributing to atherosclerosis and cardiovascular disease. 23,24 In several clinical studies, elevated apoC-III in HDL and non-HDL fractions was a significant predictor of coronary events and progression of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of apoC-III at the surface of LpC-III:B also reduces the ability of this particle to bind cellular receptors in vitro. 28,29 Plasma lipoprotein particle levels are sensitive to changes in their constituent apolipoprotein. For instance the concentration of LpC-III:B is increased after ingestion of a fatty meal 25 and in patients with hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%